A High-resolution Typing Assay for Uropathogenic Escherichia coli Based on Fimbrial Diversity - Ren, Yi; Palusiak, Agata; Wang, Wei; Wang, Yi; Li, Xiao; Wei, Huiting; Kong, Qingke; Rozalski, Antoni; Yao, Zhi; Wang, Quan (Frontiers in Microbiology, 2016)
Urinary tract infections (UTIs) are one of the most common bacterial infections in humans, causing cystitis, pyelonephritis, and renal failure. Uropathogenic Escherichia coli (UPEC) is the leading cause of UTIs. Accurate and rapid discrimination of UPEC lineages is useful for epidemiological surveillance. Fimbriae are necessary for the adherence of UPEC strains to host uroepithelia, and seem to be abundant and diverse in UPEC strains. By analyzing all the possible fimbrial operons in UPEC strains, we found that closely related strains had similar types of chaperone-usher fimbriae, and the diversity of fimbrial genes was higher than that of multilocus sequence typing (MLST) genes. A typing assay based on the polymorphism of four gene sequences (three fimbrial genes and one housekeeping gene) and the diversity of fimbriae present was developed. By comparison with the MLST, whole-genome sequence (WGS) and fumC/fimH typing methods, this was shown to be accurate and have high resolution, and it was also relatively inexpensive and easy to perform. The assay can supply more discriminatory information for UPEC lineages, and have the potential to be applied in epidemiological surveillance of UPEC isolates.